PP.24.09: A PILOT STUDY TO ASSESS EFFECTS OF ALENDRONIC ACID ON AORTIC CALCIFICATION AND STIFFNESS IN POSTMENOPAUSAL WOMEN. (June 2015) - Cecelja, M.; Edwards, S.; Moore, A.; Fogelman, I.; Chowienczyk, P.; Frost, M.
Abstract : Objective: Vascular calcification, potentially contributing to aortic stiffening, is now recognised to be a highly regulated process resembling osteogenesis. Bone-related proteins involved in osteogenesis may regulate vascular calcification and bisphosphonates, used for treatment for osteoporosis, may have the potential to decrease vascular calcification. The aim of this pilot study was to investigate the effect of alendronic acid on vascular calcification and arterial stiffness. Design and method: In an open-label, randomised controlled study, in postmenopausal women evaluated to be osteopenic or osteoporotic, six women (mean age 58 +/- 4.8 years) were studied before and during treatment with alendronate (70 mg weekly). Nine women (mean age 59 +/- 3.5 years) were randomised to calcium and vitamin D only. Abdominal aortic calcification (AAC) was measured using a high-definition instant vertebral assessment (DXA-IVA) scan. A previously validated semi-quantitative 24-point score was used to quantify AAC. Carotid-femoral pulse wave velocity (PWV) was measured using the Sphygmocor system (Atcor Medical). Measurements were made at baseline and after 6 and 12 months. Results: In women undergoing alendronate therapy, AAC was significantly reduced over the 12 month follow-up period with mean scores at baseline, 6 months and 12 months of 2.6, 1.6 and 0.4 arbitrary units, respectively (p < 0.05). In contrast, there was no significant change in PWV between the time points after adjustment for MAP and HR (mean values at baseline, 6 and 12 months were 8.15 (confidence intervals (CI): 7.2–9.2), 8.71 (CI: 7.7–9.7) and 9.2 (CI: 8.2–10.2) m/sec respectively, P = 0.419). In women randomised to calcium and vitamin D, there was no significant change in AAC over the follow-up period with mean scores at baseline, 6 months and 12 months of 3.43, 0.42 and 2.0 arbitrary units, respectively, nor was there significant change in PWV. Conclusions: This pilot study suggests that alendronate therapy may reduce reduction AAC as detected by DXA imaging.